Role of exogenous interleukin 4 in the dynamics of acute liver injury. (23rd February 2017) - Lynch, Ruairi; Hawley, Cathy; Bain, Calum; Jenkins, Stephen
Abstract: Background: Mortality in acute liver failure is very high, and the only reliable treatment is transplantation. Interleukin 4 (IL4) has pleiotropic effects on a network of cells directing repair, regeneration, and fibrosis. Pretreatment with subcutaneous IL4 complexed with anti-IL4 antibody (IL4c) promotes repair of carbon tetrachloride-mediated murine liver injury by stimulating hepatocyte proliferation. We hypothesised that IL4c could be administered therapeutically and act by a variety of mechanisms beyond engagement of hepatocytes. Methods: C57Bl/6 mice were given carbon tetrachloride intraperitoneally to induce acute liver injury. Preinjury and postinjury dosing regimens of IL4c were compared. The role of IL4 receptor α-chain (IL4Rα) signalling in bone-marrow-derived cells was investigated using tissue-protected chimeras generated with wild type or IL4Rα −/– donor bone marrow. Liver was analysed by immunohistochemistry and fluorescence-activated cell sorting (FACS). Findings: When compared with vehicle, administration of IL4c after injury produced a significant reduction in mean alanine aminotransferase (242 U/L [61·9] vs 131 [30·8], p<0·0001) and necrotic cell area (11·6% [7·04] vs 0·36 [0·6], p<0·0001). Although necrosis was reduced, the necrotic area in IL4c-treated liver was not replaced with hepatocytes but with a cellular infiltrate characterised by high F4/80 expression. FACs analysis showed a reduced proportion and number of Ly6c hi MHCII lo monocytes and a concomitant increase in the number of Ly6c lo MHCII hi F4/80 hi macrophages in injured livers treated with IL4c. This phenotypic change was dependent on IL4c signalling to Ly6c hi MHCII lo monocytes, since these cells exhibited developmental arrest when derived from IL4Rα-deficient bone marrow in chimeric mice. Interpretation: We demonstrate that IL4c can be administered therapeutically after carbon tetrachloride injury to improve indices of hepatic injury. Furthermore, IL4c treatment mediates a change in the monocyte–macrophage compartment which is consistent with a switch from a proinflammatory (Ly6c hi ) to a proreparative (Ly6c lo ) macrophage phenotype. We postulate that these Ly6c lo macrophages mediate clearance of necrotic debris and facilitate hepatic regeneration. Funding: Wellcome Trust.